The Current Status of Corpus Linguistics in Russian Linguistics (Shuneyko, A. A. : Корпусная лингвистика. Учебник для вузов. 2020. Moscow, Yurayt ISBN 978-5-534-13603-6) - Györfi, Beáta (Slavica, 2021)
Corpus linguistics is a relatively new, however rapidly developing area of linguistics. Nevertheless, the methodology of corpus research and its results are scarcely applied in current linguistic research. In the present article a short overview of the history of corpus linguistics is given. The difficulties of the development and spreading of this discipline in Russia is also described. A brief outline of Russian textbooks on corpus linguistics is also provided with special focus on Shuneyko’s latest work.